Opioid Abuse and Dependence During Pregnancy: Temporal Trends and Obstetrical Outcomes. Issue 4 (December 2015) - Maeda, A.; Bateman, B.T.; Clancy, C.R.; Creanga, A.A.; Leffert, L.R.
Abstract : ( Anesthesiology . 2014; 121:1158–1165)